At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Get immediate and reliable solutions to your questions from a knowledgeable community of professionals on our platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

I will give you brainliest . Help

I Will Give You Brainliest Help class=

Sagot :

Answer:

x = 8.64

x = - 7.64

Both to 2 d.p

Step-by-step explanation:

Firstly, - 8 both side - cancels the +8 & get the surd to equal x - 8

Then, square root both side, to get:

x-2= x^2 - 64

+ 2 both side

x = x^2 - 66

-x

0= x^2 - 66 - x

x^2 - x - 66 = 0

general equation for quadratic is ax^2 + bx + c

Now, we can find the value of a, b, c using x^2 - x - 66 = 0

a=1

b= - 1

c= - 66

Now use quadratic formula

x = -b±√(b²-4ac))/(2a

= --1 + √ - 1 x - 1 - 4x1x-66 / 2x1

= 8.639.....

Now repeat with - b - & not - b +

x = -b±√(b²-4ac))/(2a

= --1 - √ - 1 x - 1 - 4x1x-66 / 2x1

= - 7.639.......